2010
DOI: 10.4049/jimmunol.1001459
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyuridine Triphosphate Incorporation during Somatic Hypermutation of Mouse VkOx Genes after Immunization with Phenyloxazolone

Abstract: Somatic hypermutation (SHM) of Ig genes is the result of a two-phase process initiated by activation-induced cytidine deaminase, relying on two different strategies for the introduction of mutations at CG pairs (phase I) and at AT pairs (phase II). To explain the selectivity of phase II, two mechanisms were proposed: AT-selective error-prone DNA-polymerases, deoxyuridine triphosphate (dUTP) incorporation, or both. However, there has been no experimental evidence so far of the possible involvement of the latter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…It has been proposed that a DNA polymerase might use this non-canonical base from the nucleotide pool to fill gaps produced during SHM 39,40 . To test that hypothesis, we first did DNA-replication assays on a primer-template substrate (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proposed that a DNA polymerase might use this non-canonical base from the nucleotide pool to fill gaps produced during SHM 39,40 . To test that hypothesis, we first did DNA-replication assays on a primer-template substrate (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although directed cytosine deamination by the enzyme AID is the major source of uracil during these processes, direct incorporation of dUTP by DNA polymerase has not yet been ruled out as a minor contributor 107 . It was recently reported, for example, that uracil can be detected at positions of thymines in the variable region of mouse immunoglobulin genes 108 . Another study concluded, however, that uracil in hypermutating immunoglobulin genes was only found at positions of cytosines 109 .…”
Section: Transcription-associated Changes In Dna Compositionmentioning
confidence: 99%
“…The only reports of uracils created by AID in normal B cells have been in mouse models of antibody maturation that have focused only on the Ig genes (25,26). Furthermore, the balance between uracil creation in the B cell genome by AID and its removal by UNG2 or other repair enzymes has not been examined.…”
mentioning
confidence: 99%